Acute performance enhancement following squats combined with elastic bands on short sprint and vertical jump height in female athletes - Krcmár, M.; Krcmárová, B.; Bakalár, I.; Šimonek, J. (The Journal of Strength and Conditioning Research, 2021)
The main purpose of this study was to compare back squats with and without elastic bands on sprint and vertical jump height. Fourteen female athletes (21.9 ± 2.3 years; 177.5 ± 6.36 cm; 66.2 ± 6.2 kg; 1 repetition maximum [1RM]/ body mass: 1.96 ± 0.14) agreed to participate. On 4 separate days, athletes walked freely for 5 minutes (CON), performed 3 sets of 4 repetitions at 85% of their 1RM with 20% or 30% (BAND20 or BAND30) of the total resistance originated from elastic bands, or performed 3 sets and 4 repetitions at 85% of their 1RM with an isoinertial load (ISO) before performance tests. Posttesting began 5 and 10 minutes after the last set of squats and included sprints over 3, 5, and 10-m, squat jump (SJ), and countermovement (CMJ) vertical jump height. The results of this study show that all postactivation performance enhancement (PAPE) protocols significantly improved 10-m sprint time (p < 0.05 to p < 0.01). Only BAND30 significantly improved 3-m and 5-m sprint times at both times of posttesting (p < 0.01). Comparison of PAPE protocols showed a significant difference when comparing BAND30 vs. ISO in SJ height in favor of BAND30 only when the best SJ height results from both posttesting times were selected (p < 0.01, g = 1.08). The results of this study suggest that all PAPE protocols were able to enhance short sprints and vertical jump height, but it seems that there is a greater trend to achieve better performance after performing the BAND30 protocol that can be seen by higher effect sizes achieved almost in all tests compared with the other PAPE protocols.